Human Papilloma Virus Identification in Breast Cancer Patients with Previous Cervical Neoplasia - Lawson, James S.; Glenn, Wendy K.; Salyakina, Daria; Clay, Rosemary; Delprado, Warick; Cheerala, Bharathi; Tran, Dinh D.; Ngan, Christopher C.; Miyauchi, Shingo; Karim, Martha; Antonsson, Annika; Whitaker, Noel J. (Frontiers in Oncology, 2016)
Purpose: Women with human papilloma virus (HPV) associated cervical neoplasia have a higher risk of developing breast cancer than the general female population. The purpose of this study was to (i) identify high risk for cancer HPVs in cervical neoplasia and subsequent HPV positive breast cancers which developed in the same patients and (ii) determine if these HPVs were biologically active. Methods: A range of polymerase chain reaction (PCR) and immunohistochemical techniques were used to conduct a retrospective cohort study of cervical precancers and subsequent breast cancers in the same patients. Results: The same high risk HPV types were identified in both the cervical and breast specimens in 13 (46%) of 28 patients. HPV type 18 was the most prevalent. HPVs appeared to be biologically active as demonstrated by the expression of HPV E7 proteins and the presence of HPV associated koilocytes. The average age of these patients diagnosed with breast cancer following prior cervical precancer was 51 years, as compared to 60 years for all women with breast cancer (p for difference = 0.001). Conclusions: These findings indicate that high risk HPVs can be associated with cervical neoplasia and subsequent young age breast cancer. However these associations are unusual and are a very small proportion of breast cancers. These outcomes confirm and extend the observations of 2 similar previous studies and offer one explanation for the increased prevalence of serious invasive breast cancer among young women.